Negritude in an unlikely place: representation of the Nuosu and the African in Jidi Majia’s paroles de feu - (:unkn) unknown (My University, 2022)
In a rare occurrence, contemporary Chinese poetry encounters history of the African struggle for identity restoration and the revalorization of culture in Jidi Majia’s Paroles de feu. This article navigates this unique connection by highlighting the interconnectedness of the African’s experiences with those of other marginalized groups globally. Jidi Majia successfully locates these experiences within the context of Negritude and its influence in the identity struggles of several other groups around the world. In Paroles de feu, this inspiration is laid bare through a carefully crafted connection between the Negritude movement and Jidi Majia’s representation of his Chinese ethnic Nuosu/Yi minority. The poet directly engages Negritude by replicating its very pillars in celebrating his ethnicity. Through this, he also engages our memory of Negritude as a literary movement and leaves a remarkable impression of the movement as inspiring poetry beyond the world of the African.
Keywords: African Research